Virtue hoarders : the case against the professional managerial class - Liu, Catherine (Forerunners (Minneapolis, Minn.), 2021)
Author Catherine Liu shows how Professional Managerial Class (PMC) elite workers who labor in a world of performative identity and virtue signaling stand in the way of social justice and economic redistribution. Virtue Hoarders is an unapologetically polemical call to reject making a virtue out of taste and consumption habits.--Publishers website